GENETIC VARIABILITY OF ARROWROOT (Maranta Arundinacea L.) IN YOGYAKARTA PROVINCE, INDONESIA BASED ON ISSR ANALYSIS - Bernardinus Pratama; Purnomo Purnomo; Budi Setiadi Daryono (BIOTROPIA, 2022)
The cultivation of arrowroot (Maranta arundinacea L.) in Indonesia, particularly in Yogyakarta Province has a great potential to be developed. This study aims to determine the genetic variability and analyze the intraspecific relation of arrowroot using Inter Simple Sequence Repeats (ISSR) markers as basic informations for considerations in the character selection of arrowroot cultivation in Yogyakarta. Exploratory survey method was occured in Gunungkidul, Kulon Progo, Sleman, and Bantul Districts to collect cultivar accessions. Accessions were replanted in Sawitsari Research Station. DNA isolation from the leaves of 7 moths old accessions was done using CTAB buffer solution. The DNA fingerprinting analysis was carried out using the result of DNA amplification with 4 ISSR markers. The polymorphism data then used for phenetic analysis using UPGMA algorithm and Baroni-Urbani Busser similarity coefficient to form dendrogram. Total of 5 local cultivars were found, identified as ‘Sili’, ‘Sembowo’,’ Sugo’, ‘Kebo’, and ‘Teropng’, each showed distinct rhizome morphological characters. The ISSR-PCR analysis resulted high polymorphism with 68,17% polymorphism mean and mean of polymorphic band was 6,75. Dendrogram resulted 4 clusters in 80% similarity index. Cluster A, B.I., and B.II.b consisted of ‘Sili’, ‘Teropong’, and ‘Kebo’ cultivars, respectively, while the cluster B.II.a gathered ‘Sugo’and ‘Sembowo’ cultivars.